2020
DOI: 10.1111/iju.14336
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral location is associated with survival outcomes in upper tract urothelial carcinoma: A population‐based analysis

Abstract: Objectives: To evaluate the prognostic value of tumor location in patients with upper tract urothelial carcinoma. Methods: Within the Surveillance, Epidemiology and End Results Incidence Database, 6619 upper tract urothelial carcinoma cases were identified, including 3719 confined to the renal pelvis and 2971 to the ureter. Predictors of surgical technique (kidney sparing surgery versus radical nephroureterectomy), as well as 2-and 5-year cancer-specific survival and overall survival were evaluated. Results: M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Data for CSS were extractable from 14 studies [8,9,[11][12][13][15][16][17][18][19][20][21]23,24]. Pooled results indicated that patients with UT had significantly worse CSS after RNU (HR: 1.37, 95% CI: 1.19-1.57, p < 0.001) compared to patients with RPT (Figure 3).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data for CSS were extractable from 14 studies [8,9,[11][12][13][15][16][17][18][19][20][21]23,24]. Pooled results indicated that patients with UT had significantly worse CSS after RNU (HR: 1.37, 95% CI: 1.19-1.57, p < 0.001) compared to patients with RPT (Figure 3).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Significant between-study heterogeneity was observed (p = 0.03 and I 2 = 47%); thus, a random-effect model was used for data synthesis. Data for OS were extractable from 7 studies [8,[14][15][16]18,19,23]. A pooled results indicated that patients with UT had significantly worse OS after RNU (HR: 1.26, 95% CI: 1.08-1.46, p = 0.003) compared to patients with RPT (Figure 4).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 3 more Smart Citations